2013
DOI: 10.4103/2230-8229.122023
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat poisoning: A case report and review of literature

Abstract: Paraquat (1, r-dimethyl-4,4’-bipyridium dichloride), a brown syrupy liquid is an effective herbicide that has low chronic toxicity because of its rapid deactivation on contact with soil. A high dose of paraquat or severe poisoning has a poor prognosis. At present there is no specific antidote to paraquat poisoning, hence the need to focus on prevention and in case of exposure or ingestion, aggressive decontamination to prevent further absorption. Although uncommon, paraquat ingestion can lead to severe and oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
(42 reference statements)
0
23
0
3
Order By: Relevance
“…Paraquat poisoning has been well known to elicit overt ROS accumulation and oxidative stress along with profound inflammatory responses (Brooks, ; Bus et al, ; Ge et al, ; Raghu et al, ). Data from our present study revealed that acute paraquat exposure compromised myocardial and cardiomyocyte sarcomere contractile function manifested as enlarged LVESD, reduced fractional shortening, sarcomere shortening capacity, and maximal velocities of sarcomere shortening/relengthening.…”
Section: Discussionmentioning
confidence: 99%
“…Paraquat poisoning has been well known to elicit overt ROS accumulation and oxidative stress along with profound inflammatory responses (Brooks, ; Bus et al, ; Ge et al, ; Raghu et al, ). Data from our present study revealed that acute paraquat exposure compromised myocardial and cardiomyocyte sarcomere contractile function manifested as enlarged LVESD, reduced fractional shortening, sarcomere shortening capacity, and maximal velocities of sarcomere shortening/relengthening.…”
Section: Discussionmentioning
confidence: 99%
“…Addo and Poon-King (1986) claimed a 72% survival rate in 72 patients treated with CP (5 mg/kg/d to a maximum total of 4 g) and dexamethasone (8 mg eight-hourly over two weeks) [7]. Lin et al, 1999; reported results of a prospective, randomized study of pulse therapy with cyclophosphamide (1g/d for 2 d) and methylprednisolone (1g/d for 3 d) in 142 patients of paraquat poisoning [1].…”
Section: Discussionmentioning
confidence: 99%
“…Paraquat (1,1′‐dimethyl‐4,4′‐bipyridinium; PQ) is one of the most widely used nonselective dipyridyl herbicides and is a serious hazard to the health of humans and animals . The lungs are the primary target organ of PQ, and respiratory failure resulting from severe lung inflammation and interstitial fibrosis is one of the leading causes of death . Previous research has found that PQ has an adverse effect on the liver, kidneys, brain, and other organs.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The lungs are the primary target organ of PQ, and respiratory failure resulting from severe lung inflammation and interstitial fibrosis is one of the leading causes of death. [3,4] Previous research has found that PQ has an adverse effect on the liver, kidneys, brain, and other organs. However, the effect of PQ on the male reproductive system is still not well understood.…”
Section: Introductionmentioning
confidence: 99%